Sue Bridehead: Hardy's feminist figure or a fallen temptress - Sivandipour, Faezeh; Talif, Rosli (Universiti Putra Malaysia Press, 2018)
Among Thomas Hardy's female characters, Sue Bridehead (the female protagonist in Jude the Obscure 1895) seems very powerful and many readers may consider her as Hardy's feminist female character, who stands against all the existing forces of her time and wants to defend her status quo. Reading this article clarifies that, although Sue wants to say something new in women's case, she is not supported through the story and rather her portrayal shows that a woman, in the Victorian society, is the weaker sex and even if she wants to change or break the rules she cannot simply because she is a woman. Therefore, portrayal of Sue supports this idea that, while Hardy highlights women's problems and inequalities it is merely to emphasise the existing social and religious situations of the Victorian era. In this light, Hardy's portrayal of Sue does not follow the basic tenets of Christian feminism. This article, considering the main images of sin, salvation and Eve (a temptress), illustrates that Hardy's portrayal of Sue is not in accordance with Christian feminism; therefore, Sue cannot be considered as Hardy's feminist figure.